Perbandingan Klasifikasi Emosi Tokoh Utama Dalam Novel Hujan Karya Tere Liye Dengan Novel Dry Karya Neal Shusterman Dan Jarrod Shusterman - Yurika Sephiani; Dian Hartati (Jurnal Ilmiah Wahana Pendidikan, 2022)
The novel Hujan by Tere Liye and the novel Dry by Neal Shusterman and Jarrod Shusterman were chosen to compare the classification of the main character's emotions towards disasters and personal problems experienced by the main character Hujan by Tere Liye with the novel Dry by Neal Shusterman and Jarrod Shusterman. The research method used is descriptive analysis with an analysis knife of emotional classification proposed by Minderop. The reading and note technique was used as a data collection technique. The results of the study are: (1) the emotional similarities of the main characters of the two novels are that there are five types of emotions, namely guilt, shame, sadness, hatred and love. (2) the difference in the emotions of the main characters of the two novels is that the novel Hujan by Tere Liye has seven types of emotions, namely guilt, pent-up guilt, self-punishment, shame, sadness, hatred and love. While the novel Dry by Neal Shusterman and Jarrod Shusterman has five types of emotions, namely guilt, shame, sadness, hatred and love..